2016
DOI: 10.1111/apt.13800
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: fundic gland polyps and proton pump inhibitors

Abstract: Proton pump inhibitor usage is associated with a significantly increased prevalence of fundic gland polyps, and there is a trend for this to increase with longer length of PPI exposure. However, the meta-analysis is limited mainly to cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 50 publications
4
45
1
2
Order By: Relevance
“…PPI treatment also induces foveolar epithelial cell hyperplasia and foveolar hyperplastic polyps . Furthermore, recent studies have shown that patients on PPIs have a larger size and a higher incidence of FGPs than those not on PPIs . Two systematic reviews showed an increased risk of FGPs with long‐term PPI treatment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPI treatment also induces foveolar epithelial cell hyperplasia and foveolar hyperplastic polyps . Furthermore, recent studies have shown that patients on PPIs have a larger size and a higher incidence of FGPs than those not on PPIs . Two systematic reviews showed an increased risk of FGPs with long‐term PPI treatment .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Furthermore, recent studies have shown that patients on PPIs have a larger size and a higher incidence of FGPs than those not on PPIs. 14,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Two systematic reviews showed an increased risk of FGPs with long-term PPI treatment. 34,35 Even though these reports showed the association between PPIs and FGPs, they did not clarify the histological changes of FGPs after PPI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent meta-analysis revealed an increase in FGP's amongst PPI users compared to controls (OR 2.46, 95% CI 1.42-4.27, P = 0.001). Especially if the drugs were taken for a longer period of time [7].…”
Section: Resultsmentioning
confidence: 99%
“…They are found in up to 23% of endoscopies, and dysplasia is found in < 1% of these polyps [28]. The mechanism involved in the increased prevalence of FGP in PPI users is still uncertain, but one hypothesis is that fundic gland cysts are caused by mucus blocking of the fundic pits [29]. …”
Section: Proposed Side Effects Of Ppismentioning
confidence: 99%